Analysis of the effects of density profile on the bending properties of particleboard using finite element method (FEM) - Wong, E.-D.; Yang, P.; Zhang, M.; Wang, Q.; Nakao, T.; Li, K.-F.; Kawai, S. (Springer Science and Business Media LLC, 2003)
The bending properties of particleboards with various density profiles were analyzed by calculating their modulus of elasticity (MOE) using two-dimensional finite element method (FEM). The calculation was based on the fundamental properties of homo-profile particleboards (board with flat density profile) produced from lauan (Shorea spp.) particles and an isocyanate resin. The results are summarized as follows: 1. The calculated MOE fit very well with the experimental values, with a deviation of below 5% 2. Increment in peak density (PD) results in a proportional increase in MOE, while core density (CD) determines the optimum slope gradient between the peak and core regions. 3. The counteractive effect arising from increment in PD and simultaneous reduction in peak width resulted in merely 9% improvement in MOE, when PD was increased from 1.0 to 1.5 g/cm3. 4. Increment in peak distance (Pdi) results in a proportional reduction in MOE. When Pdi was doubled from 1 mm to 2 mm, MOE was reduced by about 11%. 5. In idealized density profile models, when peak and core densities remain unchanged, the maximum peak area does not necessarily result in the highest MOE. 6. Multiple regression analysis shows that the overall MOE of particleboard depends basically on the board mean density (MD), PD and Pdi.